Vagaries and challenges confronting police accountability in the South African post-colony as revealed by recent Commissions of Inquiry - Van Der Spuy, Elrena (International journal of comparative and applied criminal justice, 2021)
This paper takes inspiration from David Bayley’s recognition that Commissions of Inquiry yield useful archival material for investigating the challenges for police accountability. Guided by his spirit of inquiry, this paper presents three recent Commissions of Inquiry in South Africa (the Khayelitsha Commission of Inquiry and the Inquiry into the events at Marikana; and the yet to be completed Zondo Commission of Inquiry into State Capture) and considers how each have shed light on the organisational woes and policy conundrums confronting the police and policing in South Africa. In turn, these Commissions have yielded spaces for (re-)engaging issues relating to the structure, function and governance of the police. In doing so, the deliberations of these Commissions have in interesting ways interfaced with concerns raised in both public debates and scholarly analysis.